International consensus statement on the peri‐operative management of anaemia and iron deficiency. (20th December 2016) - Muñoz, M.; Acheson, A. G.; Auerbach, M.; Besser, M.; Habler, O.; Kehlet, H.; Liumbruno, G. M.; Lasocki, S.; Meybohm, P.; Rao Baikady, R.; Richards, T.; Shander, A.; et al.
Summary: Despite current recommendations on the management of pre‐operative anaemia, there is no pragmatic guidance for the diagnosis and management of anaemia and iron deficiency in surgical patients. A number of experienced researchers and clinicians took part in an expert workshop and developed the following consensus statement. After presentation of our own research data and local policies and procedures, appropriate relevant literature was reviewed and discussed. We developed a series of best‐practice and evidence‐based statements to advise on patient care with respect to anaemia and iron deficiency in the peri‐operative period. These statements include: a diagnostic approach for anaemia and iron deficiency in surgical patients; identification of patients appropriate for treatment; and advice on practical management and follow‐up. We urge anaesthetists and peri‐operative physicians to embrace these recommendations, and hospital administrators to enable implementation of these concepts by allocating adequate resources.